The effects of breathing and coughing exercises on respiratory parameters in COVID-19 patients - Uçar, Özge; Çelik, Sevim; Uzun, Suna; Karahan, Elif; Altıntaş, Sibel (Rzeszów University Press, 2026)
Introduction and aim. COVID-19 primarily affects the respiratory system, often resulting in pneumonia and dyspnea that may persist after recovery. This study aimed to evaluate the effect of deep breathing and coughing exercises using a Triflow device on respiratory parameters in patients with COVID-19 pneumonia. Material and methods. This single-blinded randomized controlled study was conducted with 326 patients diagnosed with COVID-19 pneumonia. Participants were randomly assigned to an experimental group (n=163) or a control group (n=163). The experimental group performed exercises for 10 consecutive days. The control group received routine hospital care, which included routine nurse-led monitoring of vital signs, peripheral oxygen saturation (SpO₂) assessment, medical treatment per clinical guidelines, and supportive care, but no structured breathing-exercise education. Data were analyzed using descriptive statistics, ANOVA, chi-square, and post hoc tests. Results. After 10 days of intervention, Dyspnea-12 scores decreased more markedly in the experimental group than in the control group (mean change −15 vs. −8 points; p<0.001). Arterial oxygen and SpO₂ levels also improved significantly in the experimental group compared to controls (p<0.001), while respiratory rate decreased to a greater extent (p<0.001). No adverse effects were observed. Conclusion. Deep breathing and coughing exercises with the Trilow device significantly reduced the severity of dyspnea and improved oxygenation in COVID-19 pneumonia patients. These findings suggest that incorporating structured respiratory exercises into standard care may enhance clinical outcomes and support recovery in this population.
The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of Bartın University Ethical Committee (2021-SBB-0329).
Keywords: cough exercise; COVID-19; deep breathing; nursing care; pneumonia; Triflow